The Effect of Window Width and Window-level Settings in Non-enhanced Head CT to Increase the Diagnostic Value of Subacute Ischemic Stroke - Muqmiroh, L; Setyanur, A; Maimanah, R; Witjaksono, B P (KnE Social Sciences, 2018)
Background: Non-enhanced head CT (NECT) was known as one of the modalities to assess subacute ischemic stroke. The values of window width (WW) and window level (WL) were influencing lesion conspicuity and diagnostic accuracy as well. The ability of physicians to detect parenchymal hypoattenuation depended on window width and window-level settings. Objective: To determine the best value of head NECT window width and window level in the subacute ischemic stroke. Material and method: Routine non-enhanced CT scanning was performed with the patient’s head in a head holder with a 64 Slice MSCT Light speed (GE Medical Systems) in the hospital emergency department using the following non-helical scanning technique: 120 kV, 625 mA, and 5-mm section thickness. Twenty six values of window width and window level of subacute ischemic stroke were made and assessed by 28 experienced radiologist. We found the best value of 35 WW 25 WL. This value was significantly better than brain window (p < 0.05). Conclusion: In summary, we have demonstrated that the detection of subacute ischemic stroke with non-enhanced head CT scanning was facilitated by window width and window-level settings. The 35 WW 25 WL setting was recommended to increase the diagnostic value of subacute stroke infarct. Keywords: non-enhanced head CT, subacute ischemic stroke, window width, window level